The effect of high-dose methotrexate chemotherapy on citrulline level to gastrointestinal mucositis cases in children with acute lymphoblastic leukemia during the consolidation phase - Rahmayani, Susanti; Athiyyah, Alpha Fardah; Ranuh, I.G.M Reza Gunadi; Darma, Andy; Sumitro, Khadijah Rizky; Andarsini, Mia Ratwita; Sudarmo, Subijanto Marto (Edelweiss Applied Science and Technology, 2025)
Acute Lymphoblastic Leukemia (ALL) is the most common pediatric malignancy, with survival rates exceeding 90% due to advancements in chemotherapy, including high-dose methotrexate (HD-MTX). However, gastrointestinal (GI) mucositis remains a significant complication, impairing treatment continuity and quality of life. Citrulline, a biomarker synthesized in enterocytes, reflects intestinal integrity and offers a non-invasive alternative for monitoring mucosal damage. This study aimed to evaluate citrulline dynamics in children with ALL undergoing HD-MTX chemotherapy during the consolidation phase. This cross-sectional study included 34 pediatric ALL patients in consolidation phase. Serum citrulline levels were measured pre- and post-HD-MTX chemotherapy using high-performance liquid chromatography. Mucositis severity was assessed using the National Cancer Institute Common Terminology Criteria. Data analysis involved paired t-tests and subgroup comparisons by risk stratification (Standard Risk [SR], High Risk [HR]) and mucositis grades. Overall, no significant changes in serum citrulline levels were observed post-chemotherapy. SR patients exhibited a significant decline in citrulline levels, consistent with mucosal injury. Conversely, HR patients demonstrated an unexpected increase in citrulline, potentially due to compensatory enterocyte responses or altered metabolism. Grade 1 mucositis patients showed increased citrulline levels, indicating early recovery, while grade 2 mucositis patients showed no significant changes, reflecting sustained injury. Citrulline is a promising biomarker for monitoring chemotherapy-induced GI mucositis in pediatric ALL patients. Its non-invasive measurement and correlation with mucosal health highlight its potential for improving personalized care. Further validation in diverse populations is required to optimize its clinical application.